(untitled) (Agricultural Engineering, 2020)
A modern model of agriculture is based on three orders - organic, social and economic. An attempt was made in this paper to apply cluster analysis for assessment of economic and organic sustainability of organic farms. Factors that statistically influenced a decision on which farms should be recognised as sustainable were indicated. Analyses allow the following conclusion: 1) in organic farming, animal production including cattle breeding and rearing must be based on a high acreage of permanent grasslands; 2) neither the performed production processes nor the level of their automation rate or the level of organic balance do not decide on the production effectiveness, but factors of the surrounding including social factors.